(3GdehWCs - (3eGdc Hf CfS Hf eGdc GdCUHMj GdMejQj, CHh YHO Gddg, J (B179 (3g` s ((3eMeO Hf Ydi Hf YHO Gdedc Hf Ydi Hf SjO GdagQi s)
(3ChdgG (B:s
(3hbhJ GdUdGI MOKfi jMji Hf jMji Cf GdeZjQI Hf TYHI BNQ GdUdGI jheG hgh HGdchaI s
(3BNQgG (B:s
(3GSeGA GdfHi Udi Gddg Ydjg hSde s
(3QhGjI jMji Hf jMji GddjKis
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B257 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B168s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdESdGejs